(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
The research discussed in this paper situates itself within experiential and critical approaches to architectural and urban space through GPS-based mobile app technology. It uses Waze, a crowd-sourcing satellite navigation app, as its case study to discuss how the app enables new digitally mediated spatial practices performed and embodied by users. To explore how Waze informs spatial relations and practices – both physical and digital – the app is analyzed as a material object, particularly addressing the design and spatial properties of the interface, while framing it within a Cyberfeminist theoretical framework. The paper seeks to fill a gap in digital spatial theory by upholding that apps are made at a fast pace to help increase their commercial value, but their development, design, and research currently lacks critical study. As such, it looks into Waze’s implications regarding the social reconfiguration of urban relations and identity-formation. Collecting its data through a series of interviews with users as well as personal analyses, this paper aims to critically address how through its interface Waze: a) contests notions of “community” among a group of drivers on the road, b) creates transactional collaborations between Wazers, and c) sets up a digital space where users perform and move in relation to each other. The paper argues that studying Waze’s properties enables a space-based theorization of embodiment, and that through Waze’s avatars, users construct a sense of embodied self-awareness and a social understanding of their immediate context by being able to visually position themselves within an expansive network of others.